Research On The Spatial Boundary Design Of Urban Underground Space For The Composite Use Of Urban Green Space - ZHOU, Kai; LENG, Jia-Wei (MAJ - Malaysia Architectural Journal, 2025)
As urban populations grow and cities become more densely populated, the need for sustainable and liveable urban spaces has become increasingly important. Urban green space, known as the "lung of the city," plays a critical role in shaping the ecological environment of cities and enhancing the quality of life for urban residents. However, the limited availability of aboveground space has prompted a growing interest in integrating urban green space with underground space, offering a solution for more sustainable and liveable urban environments. The spatial boundary, an essential medium for exchanging material, energy and information between buildings and the natural environment, directly impacts microclimate and indoor comfort. Besides, its direct connection with nature allows renewable energy sources to provide power, which is an efficient way to minimise environmental impacts. This study seeks to identify the commonly used forms of spatial boundaries and analyse their relationship with building performance. Specifically, the research focuses on relevant prototypes of spatial boundaries in the Yangtze River Delta's most densely populated cities (over 1,000 persons per sq. km), including Shanghai, Wuxi, Nanjing, and Suzhou. By examining spatial boundaries in selected cases, the study explores their impact on building performance and summarises the frequently used forms of spatial boundaries, highlighting their role in regulating building performance. The findings offer valuable insights for constructing modern urban green space systems and contribute to the advancement of three-dimensional urban planning, ultimately aiding in the creation of sustainable and liveable urban spaces and fostering a better understanding of the benefits of integrating underground space with urban green space.